2017
DOI: 10.1002/dev.21581
|View full text |Cite
|
Sign up to set email alerts
|

Developmental social isolation affects adult behavior, social interaction, and dopamine metabolite levels in zebrafish

Abstract: The zebrafish is a social vertebrate and an excellent translational model for a variety of human disorders. Abnormal social behavior is a hallmark of several human brain disorders. Social behavioral problems can arise as a result of adverse early social environment. Little is known about the effects of early social isolation in adult zebrafish. We compared zebrafish that were isolated for either short (7 days) or long duration (180 days) to socially housed zebrafish, testing their behavior across ontogenesis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 92 publications
7
78
2
Order By: Relevance
“…Our findings regarding brain 5-HT levels are in contradiction with previous reports, however, this discrepancy might be explained by the facts that in these papers either i.) only extracellular 5-HT content was measured and ii) adult animals were employed (Maximino et al, 2013b) or iii) social isolation was conducted in adult fish or in larvae from the age of 0 dpf (Shams et al, 2017a, 2017b, 2015). The latter case, together with rodent data supports that the period during which isolation occurs is fundamental regarding later consequences, highlighting the importance of critical and sensitive developmental periods (Einon and Morgan, 1977; Fone and Porkess, 2008; Hall, 1998; Lukkes et al, 2009a).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings regarding brain 5-HT levels are in contradiction with previous reports, however, this discrepancy might be explained by the facts that in these papers either i.) only extracellular 5-HT content was measured and ii) adult animals were employed (Maximino et al, 2013b) or iii) social isolation was conducted in adult fish or in larvae from the age of 0 dpf (Shams et al, 2017a, 2017b, 2015). The latter case, together with rodent data supports that the period during which isolation occurs is fundamental regarding later consequences, highlighting the importance of critical and sensitive developmental periods (Einon and Morgan, 1977; Fone and Porkess, 2008; Hall, 1998; Lukkes et al, 2009a).…”
Section: Discussioncontrasting
confidence: 99%
“…One can hypothesize that a low stress-induced cortisol response, without any change in basal levels, and the accompanying low avoidance behavior might indicate a malfunction of challenge-responding. This phenotypic background may account for low avoidance in adult and decreased locomotion in 30 dpf juvenile zebrafish after social isolation as well, observed by Shams and colleagues (Shams et al, 2017a, 2015). This theory is also supported by our findings on isolation-induced low, delayed avoidance and inadequate arousal in response to a challenge and enhanced arousal under baseline, resting conditions.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, anti-social, C (-S), fish showed a large decrease in activation in an adjacent, non-overlapping area of the ventral caudal hypothalamus ( Figure 2B and 2D, C (-S) vs C (nsc) p=0.003, Mann-Whitney test). This functional division in the hypothalamus seems to mirror the distribution of dopaminergic and serotoninergic markers (Filippi, Mahler, Schweitzer, & Driever, 2010;Lillesaar, 2011) (Figure 2C), suggesting that this area could be responsible for the changes of serotonin and dopamine levels widely reported in fish viewing social cues (Huang et al, 2015;Soaleha Shams, Amlani, Buske, Chatterjee, & Gerlai, 2018). In the preoptic area, we observed only a small dorsal (PM) increase and ventrolateral (Pa) decrease in activity, which was significant only in the Pa of anti-social control fish (C(-S) vs C (nsc) p=0.003 Mann-Whitney, Figure 2B and 2D).…”
mentioning
confidence: 62%
“…Social experiences during early development can have long lasting effects on social and other behaviors, as shown by the devastating phenotype of rhesus monkeys raised with social deprivation described by Harlow et al [1965]. Since then, numerous studies have reported effects of social isolation raising in a variety of species, including rodents [Heidbreder et al, 2000, Lukkes et al, 2009], cockroaches [Lihoreau et al, 2009], lizards [Ballen et al, 2014], mites [Schausberger et al, 2017] and fish [Hesse et al, 2015, Shams et al, 2018]. Yet, the underlying mechanisms of how social experiences shape behavior and brain development have yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%